Noam Dworman on X (X (formerly Twitter), 2023)
https://t.co/e2qv0mhD4O @BretWeinstein, I think @Yascha_Mounk (disclosure, I know him) is correctly representing your positions. After research, I made this video to demonstrate. It's edited. If you'd like me to include something from the cutting room floor, send me the TC…